2021
DOI: 10.1128/iai.00357-21
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salts Regulate Zinc Uptake and Capsule Synthesis in a Mastitis-Associated Extraintestinal Pathogenic Escherichia coli Strain

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) are major causes of urinary and bloodstream infections. ExPEC reservoirs are not completely understood. Some mastitis-associated E. coli (MAEC) strains carry genes associated with ExPEC virulence, including metal scavenging, immune avoidance, and host attachment functions. In this study, we investigated the role of the high-affinity zinc uptake ( znuABC ) system in the MAEC strain M12. El… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Interestingly, Thomas et al found a dynamic change in BA concentrations in milk after intramammary challenge with Streptococcus uberis 43 , implying the potential role of BAs in pathogen-induced mastitis. In addition, bile salts have been reported to regulate zinc uptake and capsule synthesis in a mastitis-associated pathogenic E. coli 44 , suggesting that different bile acids may have different effects on the host or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Thomas et al found a dynamic change in BA concentrations in milk after intramammary challenge with Streptococcus uberis 43 , implying the potential role of BAs in pathogen-induced mastitis. In addition, bile salts have been reported to regulate zinc uptake and capsule synthesis in a mastitis-associated pathogenic E. coli 44 , suggesting that different bile acids may have different effects on the host or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…We did find several instances of MAEC strains possessing genes with demonstrated roles in ExPEC virulence (Figure 2). Although these virulence factors were not associated with CM severity generally, it does not rule out the possibility that they contribute to the virulence of individual strains in MGs, as we have previously demonstrated for the capsule and zinc uptake gene clusters of strain M12 (21,30). Furthermore, additional factors continue to be recognized that contribute to ExPEC infections, and these may also be selected by the dairy environment and enriched in MAEC strains.…”
Section: Discussionmentioning
confidence: 69%
“…In addition to host factors, bacterial factors may also influence CM severity (17,28,29). Some MAEC strains carry virulence factors often found in human or avian extraintestinal pathogenic E. coli (ExPEC) such as toxins, siderophores, capsules and adhesins (30). For the most part, the influence of these virulence factors during intramammary infections has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, excess zinc decreases Streptococcus pyogenes hyaluronic acid capsule production by inhibiting phosphoglucomutase, a key enzyme in central carbon metabolism ( 11 ). Recent studies on Escherichia coli virulence suggest that the presence of capsule may exacerbate bile salt mediated zinc starvation ( 12 ).…”
Section: Resultsmentioning
confidence: 99%